Underpricing, Faktor Robust Ipo Pada Bursa Efek Indonesia - Arni Utamaningsih (Universitas Airlangga, 2013)
This study proves that underpricing is a robust factor on the Indonesia Stock Exchange. This research examines the pricing of IPO, the allocation of shares to groups of institutional investors, the underwriter reputation toward underpricing, price stabilization and excess returns in three regression models and some sub models. Regression results provide evidence that the IPO pricing and allocation of shares to groups of institutional investors affect the underpricing. This evidence supports book building models that developed by Benveniste and Spindt (1989). This study provides evidence that underpricing has a positive effect on price stabilization. Underpricing is also a positive effect on excess returns. Expected proceeds are strong support factor explains underpricing as a central factor. Age and expected proceeds are the support factors, together with underpricing explain price stabilization. Partial price adjustement is support factor together with underpricing explain excess returns.